Clinical profile of dengue patients: A hospital based study - Chaudhary, Vinod; Khamkar, Anil; Tiwari, Manish; Suryawanshi, Amol (Indian Journal of Child Health, 2015)
Context: For most of the patients, dengue is a self-limiting viral fever, but in some patients, it results in a life threatening condition called as dengue hemorrhagic fever or dengue shock syndrome. Objective: We attempted to determine the common and atypical clinical and laboratory features in children suffering from dengue fever, which will help in early diagnosis and management of patients suffering from dengue infection. Design: Hospital based descriptive, cross-sectional study conducted from January 2014 to December 2014. Setting: Tertiary referral teaching hospital. Patients: All patients between 1-month and 12 years admitted in pediatric ward with symptoms suggestive of dengue and who turn out to be positive for NS1 antigen alone or NS1 and immunoglobulin M antibody against dengue were included in the study. Data regarding relevant history and clinical examination and outcome and relevant investigations were collected. Results: Of 250 children included in the study, 145 (58%) were male and 105 (42%) were female. The most common presenting complaint was fever (92.8%), followed by abdominal pain (46.4%). The most common clinical sign was pyrexia followed by relative bradycardia (37.6%) and hypotension (26.4%). On laboratory investigation, the most common abnormality detected was leucopenia (81.6%) followed by thrombocytopenia (69.2%). Conclusion: A high index of suspicion is required on the part of treating pediatrician to diagnose dengue early and treat accordingly to prevent mortality due to dengue.